2017
DOI: 10.2217/nnm-2017-0225
|View full text |Cite
|
Sign up to set email alerts
|

Cell Membrane Coated Nanoparticles: next-generation Therapeutics

Abstract: Cell membrane coated nanoparticles (NPs) is a biomimetic strategy developed to engineer therapeutic devices consisting of a NP core coated with membrane derived from natural cells such as erythrocytes, white blood cells, cancer cells, stem cells, platelets or bacterial cells. These biomimetic NPs have gained a lot of attention recently owing to their cell surface mimetic features and tailored nanomaterial characteristics. They have shown strong potential in diagnostic and therapeutic applications including tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
97
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(97 citation statements)
references
References 97 publications
0
97
0
Order By: Relevance
“…In particular, the coating of nanoparticles, using the erythrocyte membranes can: i) increase the long‐circulation of nanoparticles; ii) provide their camouflage, thus avoiding the Reticuloendothelial system (RES) uptake; iii) decrease systemic clearance; iv) hamper the serum protein adsorption; v) prevent the activation of the immune system; and vi) decrease significantly the immune response. [ 139 ] Similarly, Wibroe et al. demonstrated that nanoparticles coating with erythrocytes decreased the side effects after systemic administration.…”
Section: Strategies To Overcome Side Effects Of Pegmentioning
confidence: 99%
“…In particular, the coating of nanoparticles, using the erythrocyte membranes can: i) increase the long‐circulation of nanoparticles; ii) provide their camouflage, thus avoiding the Reticuloendothelial system (RES) uptake; iii) decrease systemic clearance; iv) hamper the serum protein adsorption; v) prevent the activation of the immune system; and vi) decrease significantly the immune response. [ 139 ] Similarly, Wibroe et al. demonstrated that nanoparticles coating with erythrocytes decreased the side effects after systemic administration.…”
Section: Strategies To Overcome Side Effects Of Pegmentioning
confidence: 99%
“…The use of cancer cell plasma membranes has attracted attention because these membranes carry tumor-specific receptors and antigens that play a role in cancer cell proliferation, invasion, and metastasis. While several comprehensive reviews have summarized the applications of cell membrane camouflaged NPs (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46) from various cell sources, to the best of our knowledge only one of these reviews is focused on advances with CCMCNPs (37).…”
Section: Introductionmentioning
confidence: 99%
“…Particles 1-1,000 nm in size are defined as nanoparticles and offer good drug delivery characteristics. Nanoparticles 10-100 nm in size are proven to offer the highest delivery efficacy (Narain et al, 2017). Various types of nanomaterials such as polymers, liposomes, and metals have been developed for the delivery of therapeutic agents for cancer treatment.…”
Section: Introductionmentioning
confidence: 99%